TRIAL PARTICIPANTS’ ASSESSMENT OF LAW ENFORCEMENT INSTITUTIONS AND OFFICERS’ BEHAVIOUR: THE DATA OF 2012 AND 2015 YEAR STUDIES - Valickas, Gintautas; Vanagaitė, Kristina (Teisė, 2017)
The article analyses how the participants of the hearings of various Lithuanian courts assess law enforcement institutions, their own commitment to obey the law and law enforcement officers, the behaviour of relevant officers, court premises and the staff (excluding judges), as well as proposed modifications in the judicial system. Comparison of the data of 2012 and 2015 year studies in many cases revealed positive changes of participants’ evaluations.